Prevalence and risk factors of brucellosis among febrile patients attending a community hospital in south western Uganda - Migisha, Richard; Nyehangane, Dan; Boum, Yap; Page, Anne-Laure; Zúñiga-Ripa, Amaia; Conde-Álvarez, Raquel; Bagenda, Fred; Bonnet, Maryline (Scientific Reports, 2018)
Human brucellosis, a chronic disease contracted through contact with animals and consumption of unpasteurized dairy products is underreported in limited-resource countries. This cross-sectional study aimed to determine the prevalence and risk factors of brucellosis among febrile patients attending a community hospital in South western Uganda. A questionnaire that captured socio-demographic, occupational and clinical data was administered. Blood samples were tested for Brucella antibodies using Rose Bengal Plate Test (RBPT) and blood culture with standard aerobic BACTEC bottle was done. Of 235 patients enrolled, prevalence of brucellosis (RBPT or culture confirmed) was 14.9% (95% CI 10.6–20.1) with a culture confirmation in 4.3% of the participants. The factors independently associated with brucellosis were consumption of raw milk (aOR 406.15, 95% CI 47.67–3461.69); history of brucellosis in the family (aOR 9.19, 95% CI 1.98–42.54); and selling hides and skins (aOR 162.56, 95% CI 2.86–9256.31). Hepatomegaly (p < 0.001), splenomegaly (p = 0.018) and low body mass index (p = 0.032) were more common in patients with brucellosis compared to others. Our findings reveal a high prevalence of brucellosis among febrile patients and highlight a need for implementing appropriate tests, public awareness activities and vaccination of animals to control and eliminate the disease
Keywords: Brucellosis; Febrile patients; Community hospital; South western; Uganda